Buddhist Chaplaincy in the United States: Theory-Praxis Relationship in Formation and Profession - Zhen, Ven. Guan (Journal of International Buddhist Studies, 2022)
This article gives an overview of the emergence of Buddhist Chaplaincy in the US. It analyzes the concept, profession and formation of this chaplaincy using the theory-praxis model. Current available academic research literature related to this chaplaincy is also summarized and analyzed. This article puts forward potential challenges that Buddhist chaplaincy faces today in the US. It seeks possible practical and functional approaches for present and future development of Buddhist chaplaincy. Differences between practical theology and Buddhology based on the concepts of “shepherding” and “ox herding” are compared and explored. Insights on the theory-praxis model of Buddhist chaplaincy today in the US are depicted in a practical formula.